Human papillomavirus is not associated with colorectal cancer in a large international study (2010)
ABSTRACT: Objective of the study: Recent publications have reported an association between colon cancer and human papillomaviruses (HPV), suggesting that HPV infection of the colonic mucosa may contribute to the development of colorectal cancer. Methods: The GP5+/GP6+ PCR reverse line blot method was used for detection of 37 types of human papillomavirus (HPV) in DNA from paraffin-embedded or frozen tissues from patients with colorectal cancer (n = 279) and normal adjacent tissue (n = 30) in three different study populations, including samples from the United States (n = 73), Israel (n = 106) and Spain (n = 100). Additionally, SPF10 PCR was run on all samples (n = 279) and the Innogenetics INNO-LiPA assay was performed on a subset of samples (n = 15). Results: All samples were negative for all types of HPV using both the GP5+/GP6+ PCR reverse line blot method and the SPF10 INNO-LiPA method. Conclusions: We conclude that HPV types associated with malignant transformation do not meaningfully contribute to adenocarcinoma of the colon.